WRITING INTERPRETATIONS IN INDONESIA CLASSICAL AND MODERN TIMES - Muhammad Faisal (Jurnal Ilmiah Teunuleh, 2020)
The interpretation of the Qur'an has begun from the time of the Prophet (s) until it continues to develop over time, the development of interpretation of the Qur'an is inseparable from the problem of life that continues to grow according to its time. Therefore the interpretation model of the Qur'an also has characteristics, as well as different methods. The difference in interpretation model of the Qur'an also occurs in Indonesia. This article focuses on discussing the development of interpretation writing in Indonesia which is divided into two categories, namely scientific and non-scientific. In the context of socializing the worldview of the Quran, the writing of interpretations in Indonesia in the 1990s moved with two forces. First, strength in a hermeneutic context. Second, the writing of interpretation is placed as a socio-societal movement.